Experimental application results of mesenchymal stem cell microvesicles in the mouse model of acute renal failure - I. P. Ivanova; G. V. Seledtsova; V. I. Seledtsov; T. S. Khabalova; A. B. Dorzhieva (Медицинская иммунология)
An important role in restoration of damaged organs and tissues is played by mesenchymal stem cells (MSCs) and microvesicular particles (MV) produced by them. They can be a source of cytokines, anti- apoptotic and growth stimulating factors. In addition, MVs carry out transport of mRNA, miRNA, and signal proteins into damaged tissues. This increases the ability of cells to regenerate and to inhibit apoptosis, promote to angiogenesis and stimulate cell proliferation. The aim of our research was to study the immunoregulatory and pro-regenerative properties of mesenchymal stem cell microvesicles (MSC-MV) in a model of glycerol- induced acute renal failure (ARF) in mice. The experiments were carried out on CBA mice aged 3-4 months. AKI was induced by a single intramuscular injection of 50% glycerol. MSCs were obtained from the bone marrow of healthy animals and cultivated under standard conditions. Microvesicles were obtained by centrifugation at 12000g of MSC supernatant after induction of their apoptosis by culturing under oxygen deprivation conditions and in serum-free medium. MSC-MV was injected intravenously into the retroorbital sinus one day after induction of ARF. The MV dose was calculated as equivalent to (derived from) 1 million MSCs, which was 100 mL per mouse. Animals were taken out of the experiment on days 4 and 11 after MSC-MV injection. Blood plasma was taken to determine the level of creatinine, urine – for albumin analysis, kidneys – for histological examination. It has been shown that MVs induced by MSCs dose-dependently stimulated splenocyte proliferation in both spontaneous and Con-A induced tests. The addition of MV caused a decrease in doxorubicin-induced apoptosis of splenic lymphocytes in mice. Probably, in this case, MV produced by MSCs had an immunostimulatory and antiapoptotic effect. Also, MVs had a positive impact on the restoration of structure and function kidneys in a model of ARF in mice. The use of MSC-MV in treatment of acute renal failure induced by a single injection of 50% glycerol contributed to decrease albumin level urine and restoration of creatinine level in blood serum of animals. Morphological studies have shown decrease in the height cell and collecting duct diameter in the medulla and a decrease in the largest transverse diameter of superficial glomeruli in the renal cortex of sick mice. Thus, the obtained results indicate significant therapeutic and pro-regenerative properties of MSC-MV, which require further study.